Free Vibration and Buckling Analysis of Parabolic Frame Structures (International Journal of Scientific Research and Management (IJSRM), 2019)
Numerous engineering structures take place in many fields such as construction, automotive, naval industry, aerospace, etc. Parabolic frame structures have a significant role in those industries. There are many gaps in terms of the literature studies about these structures. In this paper, free vibration and buckling behavior of parabolic frame structures by using the finite element method are investigated. The structure is modeled by considering a frame element that has three degrees of freedom and neglects the displacement in y-axis. In addition, two-bay parabolic frame structure with different radius of curvature is investigated. The numerical results are compared with the CAD model of the structure by using SolidWorks for various cases. It is concluded that the results are in very good agreement with those results that are obtained from SolidWorks. It is also understood that for the different radius of curvatures the approach that is used for finite element buckling analysis in perpendicular distributed loading case does not change.